Hyperglycemia during first-line R-CHOP or dose adjusted R-EPOCH chemotherapy for non-Hodgkin lymphoma is prevalent and associated with chemotherapy alteration – a retrospective study. Issue 8 (3rd August 2018) - Lamar, Zanetta S.; Dothard, Andrew; Kennedy, LeAnne; Isom, Scott; Robinson, Mac; Vaidya, Rakhee; Hurd, David; McClain, Donald; Lesser, Glenn
Abstract: High-dose glucocorticoids such as prednisone are combined with cytotoxic chemotherapy in the R-CHOP or dose adjusted R-EPOCH regimens used for non-Hodgkin lymphoma (NHL). In this retrospective study, our primary objective was to evaluate the incidence of hyperglycemia during first-line R-CHOP or DA-EPOCH-R. The secondary objectives were to evaluate the incidence of chemotherapy alteration and overall survival in those with and without hyperglycemia. One hundred and sixty patients were eligible. We found that 47% of all patients had at least one hyperglycemic episode and hyperglycemia was associated with chemotherapy alteration ( p = .028). Multivariate analysis revealed international prognostic index (IPI) ≥ 3 ( p = .045) and chemotherapy alteration ( p = .001) were associated with decreased overall survival. We conclude that hyperglycemia is common during first-line NHL treatment with R-CHOP or DA-EPOCH-R, even in the absence of known diabetes and is associated with alterations of chemotherapy. Baseline pre-PET scan fasting blood glucose of 100 mg/dL or higher may predict hyperglycemia during therapy.